2021
DOI: 10.1186/s12877-021-02026-y
|View full text |Cite
|
Sign up to set email alerts
|

The change and correlates of healthy ageing among Chinese older adults: findings from the China health and retirement longitudinal study

Abstract: Background This study tentatively constructs a composite measure of Chinese Healthy Ageing Index (CHAI) among older adults aged 60+ and investigates change of CHAI during 2011–2015 and its association with sociodemographic characteristics. Methods Data collected from 8182 old adults aged 60+ in the 2011 and 2015 China Health and Retirement Longitudinal Study (CHARLS, a nationally representative sample) were used. Six medical measures of blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Given the multidimensional nature of healthy aging, similar to Wu et al [ 51 ], we formulated our corresponding composite measure as a CHAI score based on six physiologic domains, each empirically documented as a key indicator of mortality and a primary measure of a common age-associated chronic disease [ 52 , 53 ]: Systolic blood pressure (SBP): the average value of SBP measured three times at 45 s intervals and then grouped into three categories: 0 = ≤120 mmHg, 1 = 120–140 mmHg, and 2 = >140 mmHg. We designated respondents diagnosed with hypertension or taking anti-hypertensive medications as the unhealthiest group (score = 2) [ 2 , 51 ]; Pulmonary function: the average of expiratory peak flow (L/min) measured three times in a standing position, with gender-specific terciles grouped into three categories (for males: 0 = ≥320 L/min, 1 = 193–320 L/min, and 2 = ≤193 L/min; for females: 0 = ≥225 L/min, 1 = 153–225 L/min, and 2 = ≤153 L/min) [ 2 , 51 ]. We designated respondents diagnosed with pulmonary disease as the unhealthiest group (score = 2); Fasting glucose: classified into three categories: 0 = ≤100 mg/dL, 1 = 100–125 mg/dL, and 2 = ≥125 mg/dL [ 2 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the multidimensional nature of healthy aging, similar to Wu et al [ 51 ], we formulated our corresponding composite measure as a CHAI score based on six physiologic domains, each empirically documented as a key indicator of mortality and a primary measure of a common age-associated chronic disease [ 52 , 53 ]: Systolic blood pressure (SBP): the average value of SBP measured three times at 45 s intervals and then grouped into three categories: 0 = ≤120 mmHg, 1 = 120–140 mmHg, and 2 = >140 mmHg. We designated respondents diagnosed with hypertension or taking anti-hypertensive medications as the unhealthiest group (score = 2) [ 2 , 51 ]; Pulmonary function: the average of expiratory peak flow (L/min) measured three times in a standing position, with gender-specific terciles grouped into three categories (for males: 0 = ≥320 L/min, 1 = 193–320 L/min, and 2 = ≤193 L/min; for females: 0 = ≥225 L/min, 1 = 153–225 L/min, and 2 = ≤153 L/min) [ 2 , 51 ]. We designated respondents diagnosed with pulmonary disease as the unhealthiest group (score = 2); Fasting glucose: classified into three categories: 0 = ≤100 mg/dL, 1 = 100–125 mg/dL, and 2 = ≥125 mg/dL [ 2 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…We designated respondents diagnosed with hypertension or taking anti-hypertensive medications as the unhealthiest group (score = 2) [ 2 , 51 ]; Pulmonary function: the average of expiratory peak flow (L/min) measured three times in a standing position, with gender-specific terciles grouped into three categories (for males: 0 = ≥320 L/min, 1 = 193–320 L/min, and 2 = ≤193 L/min; for females: 0 = ≥225 L/min, 1 = 153–225 L/min, and 2 = ≤153 L/min) [ 2 , 51 ]. We designated respondents diagnosed with pulmonary disease as the unhealthiest group (score = 2); Fasting glucose: classified into three categories: 0 = ≤100 mg/dL, 1 = 100–125 mg/dL, and 2 = ≥125 mg/dL [ 2 , 51 ]. We designated respondents diagnosed with diabetes or taking antidiabetic medication as the unhealthiest group (score = 2); Cognitive function: as evaluated by the Telephone Interview for Cognitive Status (TICS), whose validity has been confirmed in different populations, including Chinese [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the older population, as age increases, food intake decreases; this is affected by factors such as society, psychology, physiology, drugs, and behavior, and ultimately leads to a high incidence of undernutrition (17,18). The reported risk of undernutrition in the people aged ≥60 years in China was 5.4%, while that in the hospitalized older individuals has been increasing continuously up to 50-70% (17,19). Studies also revealed the presence of undernutrition in 5-30% of older people living at home, 6-70% of older people in nursing homes, and 20-60% of older inpatients (20,21).…”
Section: Age Differences In Low Bmimentioning
confidence: 99%
“…As the worldwide population rapidly ages, a concurrent rapid increase in the global financial healthcare burden has been observed[ 1 ]. The resources available for daily clinical practice are generally limited.…”
Section: Introductionmentioning
confidence: 99%